Volleyball game as science and specialization in sport and p.e. - Pomohaci, M.; Sopa, I. S. (Lambert Academic Publishing, 2019)
Practicing volleyball game nowadays in large scale all over the world, is due to, beyond all doubt, it`s multiple formative and fun valences. The game of volleyball is now in continuous development, both in point of training athletes and the increases in the dynamics of phases, due to the significant progress that are more and faster in areas involving: selection, methods, physical development technical and tactical training, mental preparation and competition strategy. In a relatively short time were gathered more data on high-performance methodology, which, far from being out of knowledge, raises new and new hypotheses, whose verification and validation practice are necessary to accompany a complex design of scientific work (methodical, biophysical, neurophysiological, neuropsychological, mathematical). The book, through its contents, seeks to complete the theoretical material published in the area of the volleyball game.